How Suitable are Web Interfaces for Collaborative Learning? - Manuel Juárez Pacheco; Guillermina Waldegg Casanova (Universidad Autónoma de Baja California, 2003)
This paper describes a pilot study carried out to compare two Web interfaces used to support a collaborative learning design for science education. The study is part of a wider research project, which aims at characterizing computer software for collaborative learning in science education. The results coming from a questionnaire applied to teachers and researchers reveal the necessity to design technological tools based mainly on users' needs and to take into account the impact of these tools on the learning of curricular contents.